Off-label use of recombinant adjuvanted Herpes Zoster vaccine in a 10-year-old high-risk patient affected by epidermolysis bullosa: A case report - Claudia Palmieri; Chiara Noviello; Lorenza Moscara; Pasquale Stefanizzi; Irene Berti; Silvio Tafuri; Anna Arbo (Human Vaccines & Immunotherapeutics)
Epidermolysis bullosa is a rare genetic disorder characterized by skin fragility and blistering, resulting from mutations in dermal-epidermal junction structural proteins. Disease severity varies, with some cases involving extensive skin damage and complications secondary to chronic inflammation. Patients with immune-mediated dermatological conditions face a heightened risk of Herpes Zoster and Post-Herpetic Neuralgia, particularly during immunosuppressive treatments. A 10-year-old female with Recessive Dystrophic Epidermolysis Bullosa received off-label Recombinant adjuvanted Zoster Vaccine (RZV) – approved in individuals 18 years of age and older – before initiating Janus kinase inhibitor therapy, required to manage the underlying condition. Two standard RZV doses were administered on February 22 and April 29, 2024. No immediate vital sign alterations nor Adverse Events Following Immunization were documented in the first 7 days after immunization. A 6-month follow-up revealed no relevant emergent clinical events nor Herpes Zoster episodes. In conclusion, the case offers preliminary insights into RZV safety for high-risk pediatric patients. However, robust safety and efficacy studies are warranted to support the implementation of RZV for vulnerable individuals under 18 years of age.